A role for histone acetylation in regulating transcription elongation - Church, Michael C.; Fleming, Alastair B. (Transcription, 2018)
Recently, we reported that a major function of histone acetylation at the yeast FLO1 gene was to regulate transcription elongation. Here, we discuss possible mechanisms by which histone acetylation might regulate RNA polymerase II processivity, and comment on the contribution to transcription of chromatin remodelling at gene coding regions and promoters.